2019
DOI: 10.1038/s41598-019-41015-5
|View full text |Cite
|
Sign up to set email alerts
|

Burden of unique and low prevalence somatic mutations correlates with cancer survival

Abstract: Tumor mutational burden correlates with improved survival and immunotherapy response in some malignancies, and with tumor aggressiveness in others. To study the link between mutational burden and survival, we analyzed survival effects of tumor exonic missense mutation burden (TEMMB) across 6947 specimens spanning 31 cancers which have undergone whole exome sequencing as part of TCGA. We adjusted TEMMB for age, sex, stage, and recruitment center, and computed Cox-proportional models of TEMMB survival effects. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 32 publications
4
51
0
1
Order By: Relevance
“…TMB represents the overall amount of somatic mutations that could generate neoantigens to elicit immune response [32][33][34]. Consistently, tumors with high TMB scores contain more TILs [35] and are associated with better response to immunotherapy [36], such as melanoma [37] and NSCLC [38], with high TMB have shown better response and treatment results in immune checkpoint blockade treatment. In our analysis, we found that late-stage OCs tend to have higher TMB, which has not been described before.…”
Section: Discussionmentioning
confidence: 98%
“…TMB represents the overall amount of somatic mutations that could generate neoantigens to elicit immune response [32][33][34]. Consistently, tumors with high TMB scores contain more TILs [35] and are associated with better response to immunotherapy [36], such as melanoma [37] and NSCLC [38], with high TMB have shown better response and treatment results in immune checkpoint blockade treatment. In our analysis, we found that late-stage OCs tend to have higher TMB, which has not been described before.…”
Section: Discussionmentioning
confidence: 98%
“…And new research suggests high TMB and neoantigen load in tumors have been associated with an enhanced response to immune checkpoint blockade therapy [36] . And some researches have also shown that high TMB was inclined to confer a survival benefit in diverse cancers with more non-recurrent mutations, and higher TMB also has been reported to have higher immune infiltration in tumors [37] . Such as melanoma [38] and NSCLC [39] , with high TMB have shown better response and treatment results in immune checkpoint blockade treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TMB represents the overall amount of somatic mutations that could generate neoantigens to elicit immune response [31][32][33][34]. Consistently, tumors with high TMB scores contain more TILs and are associated with better response to immunotherapy response [35], such as melanoma [36] and nonsmallcell lung cancer (NSCLC) [37], with high TMB have shown better response and treatment results in immune checkpoint blockade treatment. However, the clinical application of TMB as a prognostic marker was both time and nancial consuming, and the predictive signi cance of TMB has been questioned by some other studies [15,16].…”
Section: Discussionmentioning
confidence: 99%